Effect of O adsorption on the electronic structure and optical properties of black phosphorene. (4th March 2022) - He, Jianlin; Liu, Guili; Wei, Lin
Abstract : The electronic structure and optical properties of the black phosphorene adsorbed O-atom system were studied by the method based on the first principle of density generalised theory with different coverage and bending angles. The black phosphorene adsorbed O-atom system is the most stable when the coverage is 5.56%. When the coverage is 8.33%, the bandgap reaches a maximum and changes from direct to indirect bandgap. The total density of states is contributed by both P and O atoms, with O atoms making the main contribution to the valence band part. With the increase of coverage, the black phosphorene adsorption O-atom system shows a blue shift at the reflection peak. With the increase of the bending angle, the adsorption energy gradually decreases and the stability of the structure decreases. The bandgap reaches the maximum at a bending angle of 5 0, and the absorption coefficient and reflectance at the absorption and reflection peaks are the smallest, and the absorption and reflection of light are the first to stop. When the bending angle is larger than 5 0, it can make the system change from indirect bandgap to direct bandgap, and it is easy to realise the stable regulation of bandgap. GRAPHICAL ABSTRACT: UF0001